Tattooing and the Risk of Wrong-Site Ear Surgery - Srouji, I (The Royal College of Surgeons of England, 2009)
Wrong-site surgery could occur in cases of bilateral pathology or in patients with normal tympanic membranes such as those undergoing stapedectomy. This report highlights the pitfalls in current surgical checklists despite best efforts being put into their design. The practice of marking the earlobe in ear surgery may be less safe than using larger arrows on the neck to indicate the side of surgery.